EFFECT OF TILLAGE, RESIDUE AND NUTRIENT MANAGEMENT ON SOIL qualities AND YIELD PARAMETERS OF RICE - Karki, Swikar; Karki, Tika Bahadur; Ramanand Yadav, Shree Chandra Shah,; Rajeev Dhakal, Ritesh Kumar Yadav,; Pandit, Madhav (Journal of Experimental Sciences)
A field experiment was conducted at Rampur, Nepal to see the effect of tillage, residue and nutrient management practices on soil properties and grain yield of rice. Three factors each with two levels i.e. tillage (with or without), residue (with or without) and nutrient management (recommended dose (RD) with 100:60:30 NPK kg ha-1 and farmer’s doses (FD) with 5Mt ha-1 of FYM + 50:23:0 NPK kg ha-1. Thus, altogether eight treatment combinations were evaluated under strip-split plot design with three replications. Higher soil organic matter was recorded in residue kept (5.73%) than the residue removed plots. Exchangeable potassium was found higher in no tillage (110.52 kg ha-1) than the conventional tillage (76.77 kg ha-1). Number of effective tillers was higher in no tillage; residue kept and recommended doses of fertilizer. Grain yield was significantly higher in no tillage with 3.66 Mt and residue kept with 3.72 Mt ha-1 compared to conventional tillage with 2.28 Mt and residue removed plots having 2.22 Mt ha-1. RD produced significantly higher grain yield of 4.53 Mt ha-1 than FD with 1.41 Mt ha-1. Therefore, untilled direct seeded rice with residue and recommend does of nutrients seem promising in Terai region of Nepal.